MULTICULTURALISM VALUES IN HENA KHAN’S AMINA’S VOICE - Nelly Trisna Raja Guk-Guk; Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2021)
Abstract This paper aims to show how the forms of multiculturalism values are displayed in Amina's life and how multiculturalism can change the perspective of other characters towards multiculturalism in the novel Amina's Voice (2017), written by a Pakistani-American writer, Hena Khan. This novel tells about a girl named Amina who has a family background from Pakistan and has long lived in Milwaukee, Wisconsin, United States. Despite living in a dominant Western culture, the Amina family consistently upholds Pakistani cultural values and uses their native customs daily. The differences between these two cultures often lead to conflicts experienced by Amina and other characters in the story. Despite encountering obstacles, Amina is shown still to practice the values of multiculturalism in her daily life. This study uses the concept of indicators of multiculturalism values proposed by Tilaar (2004) and the concept of acculturation written by Berry (2005). This research shows that there are forms of multiculturalism values found in the three spheres of Amina's life, namely in the family, school, and social environment. The indicators of multicultural values are learning in diversity, mutual trust, mutual understanding, mutual respect, open-mindedness, appreciation and interdependence (mutual dependence), and conflict resolution. In addition, the present writer also found that the practice of multiculturalism that occurred in the text resulted in an acculturation process that succeeded in changing the perspective of Amina's family members towards the value of multiculturalism. Keywords: acculturation, multicultural, multiculturalism values Abstrak Tulisan ini bertujuan untuk menunjukkan bagaimana bentuk nilai-nilai multikulturalisme ditampilkan dalam kehidupan Amina dan bagaimana praktek multikulturalisme dapat mengubah cara pandang tokoh lain terhadap multikulturalisme di dalam novel Amina’s Voice (2017) yang ditulis oleh seorang penulis Pakistan-Amerika, Hena Khan. Novel ini menceritakan tentang seorang anak perempuan bernama Amina yang memiliki latar belakang keluarga dari Pakistan yang sudah lama menetap di Milwaukee, Wisconsin, Amerika Serikat. Walaupun hidup di tengah budaya Barat yang sangat dominan, keluarga Amina secara konsisten tetap menjunjung tinggi nilai budaya Pakistan dan menggunakan adat-istiadat asal mereka di kehidupan sehari-hari mereka. Perbedaan 2 budaya ini kerap kali mendatangkan konflik yang dialami Amina dan tokoh-tokoh lain di dalam cerita. Walaupun mengalami kendala, Amina ditampilkan tetap mempraktekkan nilai-nilai multikulturalisme di dalam kehidupan sehari-harinya. Dalam penelitian ini, penulis menggunakan konsep indikator nilai-nilai multikulturalisme yang dikemukakan oleh Tilaar (2004) dan menggunakan konsep akulturasi yang ditulis oleh Berry (2005). Hasil dari penelitian ini adalah terdapat bentuk-bentuk nilai multikulturalisme yang ditemukan di tiga ruang lingkup kehidupan Amina, yaitu di lingkungan keluarga, sekolah, dan sosial. Adapun indikator nilai multikultural yang ditemukan adalah belajar hidup dalam perbedaan, membangun saling percaya, memelihara saling pengertian, menjunjung sikap saling menghargai, terbuka dalam berpikir, apresiasi dan interdepedensi, dan resolusi konflik. Selain itu, penulis juga menemukan bahwa praktek multikulturalisme yang terjadi di dalam teks menghasilkan proses akulturasi yang berhasil mengubah cara pandang anggota keluarga Amina terhadap nilai multikulturalisme. Kata Kunci: akulturasi, multikultural, nilai-nilai multikulturalisme